Voluntary settlement and its consequences on predictors of happiness: the influence of initial cultural context - Ishii, Keiko; Kitayama, Shinobu; Uchida, Yukiko (Frontiers in Psychology, 2014)
Hokkaido – a northern island of Japan that was settled by ethnic Japanese during the late 19th century and the early 20th century – may remain to be a hybrid of interdependent culture of the mainland Japan and independent culture associated with frontier settlement. We thus anticipated that contemporary Hokkaido residents would exhibit either independent or interdependent psychological profiles depending on the types of behaviors that were required in a given situation. As expected, happiness was associated with positive disengaging emotions (e.g., pride in the self) – an independent profile – in situations that required personal goal pursuit and interpersonal influence; however, happiness was associated with positive engaging emotions (e.g., feelings of closeness) – an interdependent profile – in situations that required interpersonal harmony and adjustment. In contrast, such situational dependency was not observed for either mainland Japanese or Americans. For mainland Japanese happiness was associated with positive engaging emotions whereas for Americans happiness was associated with positive disengaging emotions.